Urobilin Derived from Bilirubin Bioconversion Binds Albumin and May Interfere with Bilirubin Interacting with Albumin: Implications for Disease Pathology - Kevin I. Williams; Priyanka Suryadevara; Chang-Guo Zhan; Terry D. Hinds; Zachary A. Kipp (Biomedicines)
Background/Objectives: Bilirubin is a hydrophobic molecule that binds the carrier protein albumin for transport through systemic circulation. Bilirubin is cleared from the body through the liver and excreted into the intestines, where the microbiota modifies the chemical structure, forming urobilin, which can be reabsorbed into circulation by the hepatic portal vein. Urobilin has no known function. It is also unknown whether urobilin binds albumin for transport in circulation. We hypothesized that because of the likeness of their chemical structures, urobilin would also bind albumin like bilirubin does. Methods: First, we used in silico docking to predict if urobilin would bind to albumin and compared it to the bilirubin binding sites. To test this binding in vitro, we applied bilirubin’s fluorescent property, which occurs when it is bound to a protein, including albumin, and exposed to light. We also used this method to determine if urobilin could exhibit autofluorescence when protein bound. Results: We found that bilirubin was predicted to bind albumin at amino acids E208, K212, D237, and K240 through hydrogen bonds. However, urobilin was predicted to bind albumin using different hydrogen bonds at amino acids H67, K240, and E252. We found that urobilin has a fluorescent property that can be quantified when bound to albumin. We performed a concentration response for urobilin–albumin fluorescent binding and observed a direct relationship between the urobilin level and the fluorescence intensity. Conclusions: The in silico docking analysis and autofluorescence results demonstrate that urobilin binds to albumin and might compete with bilirubin. This is the first study to identify a urobilin-binding protein and the important aspects of its physiological function and transport in circulation.